RELATIONSHIP CORAL REEF COVER WITH REEF FISH ABUNDANCE IN THE WATERS OF MIANG ISLAND, SANGKULIRANG, KUTAI EAST, EAST KALIMANTAN - Luthfi, Oktiyas Muzaky (Directorate of Research and Community Service (DRPM), 2021)
Miang Island is located at coordinates 118° 0' 20